Multimarket Modeling of Agricultural Supply when Crop Land Is a Quasi-fixed Input: A Note - Roehlano M. Briones (Philippine Institute for Development Studies (PIDS), 2011)
Modeling of crop supply frequently adopts separate treatment of area and yield variables. The advantage of this approach is that it conveniently imposes the property of land being a quasi-fixed factor, at least on the aggregate. Given an agricultural land frontier, total supply of land may be fixed in the short run. Various crop multimarket models either ignore this property, thus foregoing the advantage of the area x yield formulation, or impose the aggregate land constraint in an ad hoc fashion. This note proposes a parsimonious area x yield framework of agricultural supply that is firmly rooted in optimization and requires minimal priors for calibration. The framework is designed for direct application in multicommodity modeling of agricultural supply and demand.
Keywords: 330; Philippines; supply response; area allocation; quasi-fixed factor